A case of malonyl coenzyme A decarboxylase deficiency with novel mutations and literature review - Zhao, Cong; Peng, Hua; Jiang, Nanchuan; Liu, Yalan; Chen, Yan; Liu, Jie; Guo, Qing; Wu, Zubo; Wang, Lin (Frontiers in Pediatrics, 2023)
Introduction Malonyl coenzyme A decarboxylase deficiency is caused by an abnormality in the MLYCD gene. The clinical manifestations of the disease involve multisystem and multiorgan. Methods We collected and analyzed a patient's clinical characteristics, genetic chain of evidence and RNA-seq. We use the search term “Malonyl-CoA Decarboxylase Deficiency” on Pubmed to collect cases reported. Results We report a 3-year-old girl who is presented with developmental retardation, myocardial damage and elevated C3DC. High-throughput sequencing identified heterozygous mutation (c.798G>A, p.Q266?) in the patient inherited from her father. The other heterozygous mutation (c.641+5G>C) was found in the patient inherited from her mother. RNA-seq showed that there were 254 differential genes in this child, among which 153 genes were up-regulated and 101 genes were down-regulated. Exon jumping events occurred in exons encoding PRMT2 on the positive chain of chromosome 21, which led to abnormal splicing of PRMT2. (P<0.05, FDR<0.05). The result of SNP showed that there were multiple mutation sites on chromosome 1, which may affect the downstream gene variation at the DNA level. The literature review identified 54 cases described since 1984. Discussion It is the first report about the locus, adding a new item to the MLYCD mutation library. Developmental retardation and cardiomyopathy are the most common clinical manifestations, with commonly elevated malonate and malonyl carnitine levels in children.